Collaborative care for pregnant women with eye conditions - Ariel Yuhan Ong; Christine A Kiire; Samantha R de Silva; Charlotte Frise (Clinical Medicine)
The management of ophthalmic conditions in pregnancy presents unique challenges that demand a nuanced approach. Significant knowledge gaps and practice variations persist, likely as a result of the infrequent nature of these issues in pregnancy, as well as the lack of crossover in the specialty training curriculum for both specialties. This commentary explores how multidisciplinary team (MDT) working can address these uncertainties to support shared decision-making and potentially improve outcomes in this vulnerable patient population. We highlight the need to involve ophthalmologists in obstetric MDTs where appropriate, and the importance of establishing clear communication channels and referral pathways between both specialties and across hospitals in the region. We also share our experience of establishing these pathways locally, the feedback we have received from interdisciplinary educational initiatives to improve knowledge sharing, and possible future directions for this collaborative approach to help fill the evidence gap.